KALIMAT IMPERATIF DALAM FILM â€œ12 YEARS A SLAVEâ€ Disutradarai oleh Steve McQueen - Maleke, Devira Claudia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is aimed to identify, classify and analyze imperative sentences in the Film â€œ12 Years a Slaveâ€ especially about its forms and functions in communication. The data are taken from the film â€œ12 Years a Slaveâ€ directed by Steve McQueen. The identification and classification of the data are based on Quirk & Greenbaum theory about forms of imperative sentence. Furthermore, there is an analysis of the data about functions of imperative sentence in communication using the theory of Aarts & Aarts.Â  In analyzing the data, the writer uses descriptive method. The problems of this research focus on the forms and functions of imperative sentence found in the film â€œ12 Years a Slaveâ€. The results of this research show that the all four kinds of forms in imperative sentence (commands without a subject, commands with a subject, commands with let, negative commands, and persuasive imperatives) are all can find in the film, and the writer also discovers a new form of imperative sentence that is used in the film which is commands using Adv & Adj. Additionally, the function of these imperative sentences found in the film are command, wish, invitation, and warning. This study concludes that the most used form in the film is commands without a subject and the most used function in the film is command. ---------------------------------------------------------------------------------------------------------- Key words: Imperative Sentence, Forms and Functions, Film â€œ12 Years a Slave.â€